A critical review of the use of holonic paradigm in traffic and transportation systems. (April 2020) - Tchappi, Igor H.; Galland, Stéphane; Kamla, Vivient Corneille; Kamgang, Jean Claude; Mualla, Yazan; Najjar, Amro; Hilaire, Vincent
Abstract: The paper presents a critical review of the use of holonic paradigm in order to model and simulate traffic and transportation systems. After an introduction presenting the principles of this paradigm as well as its frameworks and concepts, the paper surveys existing works using the holonic paradigm for traffic and transportation applications. This is followed by a detailed analysis of the results of the survey. In particular, the relevance, the design approaches and the holonification orientation methodologies are investigated. Finally, based on this extensive review, open issues of holonic paradigm in modeling and simulation of traffic and transportation models are highlighted.